Emoções de professores em pré-serviço e ensino crítico de língua adicional na Amazônia - (:unkn) unknown (Universidade Federal do Oeste do Pará, 2024)
The emotions surrounding the language teaching/learning process have recently been the target of much research. Following the same direction, this work has Applied Linguistics, as its field of analysis regarding the subjectivity of its participants, specifically regarding the teaching of additional language in the Amazon. In this context, we sought to answer the following question during the study: What is the relationship between the emotions of teachers on preservice and their perspectives on teaching English in the Amazon? Thus, the research aimed to investigate this relationship existing in the subjectivity of two participants, who are students of the Degree in English Language at the Federal University of Western Pará, thus establishing the city of Santarém, as the geographic space of the research, and therefore in the middle of the Amazon. The case study was chosen as a research methodology, using life stories, internship reports, the Tree of life tool, as well as semi-structured questionnaires with open questions as a data generating tool. The result of the research brought the theory of critical teaching of the English language to the field of discussion of emotions in this work, which has been the subject of scientific studies over the years by several authors such as Pennycook (1994), Canagarajah (2006), Kumaravadivelu (2006a), Norton and Toohey (2011). The reflection made by the study reveals that the affective aspects presented by the participants, such as strong resilience, focus on learning the English language (passion), low self-esteem, overcoming and coping, led them to express a perspective of critical teaching of the English language, therefore a decolonial teaching, as they presented the affective state of a strong desire for change in the English language teaching scenario in the Amazon.
Keywords: Emoções; Ensino crítico; Língua Inglesa; Formação de Letras; Amazônia; CNPQ:: LINGÜÍSTICA, LETRAS E ARTE